2020
DOI: 10.1186/s12944-020-01208-8
|View full text |Cite
|
Sign up to set email alerts
|

The sensibility of the new blood lipid indicator——atherogenic index of plasma (AIP) in menopausal women with coronary artery disease

Abstract: Background: Dyslipidemia is a key driver of coronary artery disease (CAD) development. This study aimed to determine whether the atherogenic index of plasma (AIP), a novel comprehensive lipid index, is an independent and reliable predictor of CAD risk in postmenopausal women. Methods: A cohort of consecutive 4644 postmenopausal women (aged 50 or above) undergoing coronary angiography (CAG) in Anzhen Hospital (Beijing, China) from January-December 2014 was included in the analysis. Of them, 3039 women were CAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
1
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 28 publications
7
45
1
3
Order By: Relevance
“…Multiple cross-sectional studies reported that AIP was a strong predictor of CAD independent of diabetes [23,24,26]. Notably, the Indian Atherosclerosis Research Study revealed that addition of AIP and family history to traditional risk factors improved risk discrimination (C-index: from 0.864 to 0.873) in Asian Indians with CAD [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple cross-sectional studies reported that AIP was a strong predictor of CAD independent of diabetes [23,24,26]. Notably, the Indian Atherosclerosis Research Study revealed that addition of AIP and family history to traditional risk factors improved risk discrimination (C-index: from 0.864 to 0.873) in Asian Indians with CAD [19].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, we presume that AIP can better re ect the lipid characteristics of diabetic patients. Recently, AIP has been demonstrated to be associated with CV morbidity and mortality in general population and different patients groups [17][18][19][20][21][22][23][24][25][26][27][28]. However, the prognostic impact of AIP on admission among T2DM patients with ACS undergoing PCI has not been exclusively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported its superiority in predicting atherosclerosis compared to traditional lipid parameters [7,8]. For example, in a large cohort study consisting of postmenopausal women undergoing coronary angiography, Guo et al demonstrated AIP to be superior to traditional lipid indices for predicting coronary artery disease in univariate as well as multivariate regression analysis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although the prevention, treatment, and care of CAD patients have greatly improved and adverse cardiovascular events and mortality have declined, the aging population experiences improved quality of life and reduced physical activity, which contributes to the prevalence of CAD remaining high and being the leading cause of death in patients with cardiovascular disease [3]. The pathogenesis of CAD is not fully understood; in addition to visceral fat, in ammatory factors, and classic clinical risk factors, researchers are committed to exploring new risk factors and biomarkers for CAD, such as the atherogenic index of plasma and the triglyceride glucose index [4,5].…”
Section: Introductionmentioning
confidence: 99%